Physical education of students in the framework of inclusive education - Maksimova, Svetlana Yu.; Mandrikov, Viktor B.; Neumoin, Valery V.; Golubin, Sergey A. (Физическое воспитание и студенческий спорт, 2023)
The article touches upon the issues of physical education in higher education within the framework of inclusive education. Its purpose is to describe the options for such organizational and substantive forms. Methods of generalization and systematization of practical experience, logical modeling are used. An algorithm for formation of an inclusive culture among medical students through volunteer activities with children with disabilities is given. Possible forms of physical education classes for students with disabilities through recreational, individual, group forms are described. The authors give an approximate algorithm for organizing a collective inclusive physical education class.